2018
DOI: 10.1021/acs.jpca.8b06787
|View full text |Cite
|
Sign up to set email alerts
|

Antiradical Activity and Mechanism of Coumarin–Chalcone Hybrids: Theoretical Insights

Abstract: In view of the multifunctional features of coumarins and chalcones, coumarin–chalcone hybrids have attracted much attention in recent years. Herein, the free radical scavenging activities of a series of coumarin–chalcone hybrids were investigated using the density functional theory (DFT) method. Three main reaction mechanisms were explored: hydrogen atom transfer (HAT), electron transfer followed by proton transfer (SET-PT), and sequential proton loss electron transfer (SPLET). Thermodynamic descriptors associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Different conformations in each case were analyzed to select the most stable structure. The B3LYP method has been successfully used in research on chalcones and other phenolic compounds. , Furthermore, Michalik and co-workers recently demonstrated that the results obtained by both B3LYP and M06-2X methods provide similar general trends, although the absolute values are somewhat different from them.…”
Section: Methodsmentioning
confidence: 98%
“…Different conformations in each case were analyzed to select the most stable structure. The B3LYP method has been successfully used in research on chalcones and other phenolic compounds. , Furthermore, Michalik and co-workers recently demonstrated that the results obtained by both B3LYP and M06-2X methods provide similar general trends, although the absolute values are somewhat different from them.…”
Section: Methodsmentioning
confidence: 98%
“…Frontier molecular orbitals (FMO) play important roles in the reactivities of molecules [29][30][31]. As shown in Figure 3, FMO orbitals are not distributed on the glycosyl group of puerarin, and the orbital shapes of puerarin and daidzein are similar, which indicates the glycosyl group unlikely participated in the reaction.…”
Section: Frontier Molecular Orbital Analysismentioning
confidence: 99%
“…According to our previous studies, [ 59,60,76 ] the s‐cis conformers of coumarin–chalcone are more stable than the s‐trans ones. Thus, in this study, only the s‐cis conformer was considered for the probe CCH .…”
Section: Resultsmentioning
confidence: 95%